The potential cost of a failed Doha Round - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2008)
In times of economic turmoil, countries might decide to increase current tariff rates to protect domestic industries or raise revenues in order to finance domestic programs. Using the highest applied or bound rate imposed by countries from 1995 to 2008 as an indicator, this study presents several scenarios regarding the economic costs of a failed Doha Round and a subsequent rush into protectionism. For example, in a scenario where the applied tariffs of major economies would go all the way up to currently bound tariff rates, world trade would decrease by 7.7 percent. In a more modest scenario where countries would raise tariffs to maximum rates applied during the past 13 years, world trade would decrease by 3.2 percent. These increases in duties would reduce world welfare by US$353 billion under the first scenario, and by US$134 billion under the more modest scenario. While such an increase in duties would particularly impact agricultural exports (–6.9 percent), especially in developing countries (–11.5 percent), exports of industrial goods could also face a substantial reduction: 2 percent in developed countries and 4.8 percent in developing countries. This study concludes there would be a potential loss of US$1,064 billion in world trade if world leaders were to fail to conclude the Doha Development Round of trade negotiations in the next few weeks and if countries were to implement subsequently protectionist policies, as occurred after the end of the Uruguay Round. The failure of the negotiations would prevent a US$336 billion increase in world trade that would have come from a reduction in tariffs and domestic support, while a worldwide resort to protectionism would contract world trade by US$728 billion.